Managing Risk of Lean Manufacturing Concept Implementation Approaching by Delphi and HOR - Widiasih, Wiwin; Karningsih, Putu Dana; Ciptomulyono, Udisubakti (Institut Teknologi Sepuluh Nopember, 2015)
The implementation of Lean Manufacturing (LM) concept was first performed at automotive industries. It is not easy being lean. Lean manufacturing concept implementation will not succeed at the first time. There were things that may have prevented the implementation meeting the objective is considered as risk. It necessary to maintain the risk of LM concept. This research will show the way for managing risk of LM implementation by Delphi and House of Risk method. This research was team up with aerospace industry in Indonesia who has been implementing LM concept. In this research, 19 risks have been identified. The rank of risk agent has been determined.